Penilaian Kinerja Berdasarkan Perspektif Balanced Scorecard Untuk Penerapan Remunerasi Pada Rs. Mata Cicendo Bandung - Rofik Sandra Herdian; Endang Wirjatmi Tri Lestari; Ely Sufianti (Jurnal Media Administrasi Terapan, 2022)
This research is about performance assessment from the balanced scorecard perspective in the framework of remuneration implementation at the Eye Hospital Cicendo Bandung. It aims to identify and analyze the employee performance at the Eye Hospital Cicendo Bandung by using 4 (four) balanced scorecard indicators. It also tries to figure out the remuneration implementation at the Eye Hospital Cicendo Bandung. This research employed a descriptive qualitative method. The data were collected through library research, interviews, and document reviews. In general, the performance assessment using the four balanced scorecard perspectives at Cicendo Eye Hospital Bandung showed good performance results. This can be seen from the achievements of each indicator in the four balanced scorecard perspectives.